Over a million students use our free study notes to help them with their homework
First note that a=eln(a) and ln(ab)=bln(a)By substituting a=3x we get a=3x=eln(3^x)=exln(3), and hence f(x)=exln(3)Answered by Christian C. • Maths tutor2583 Views
Put the equation in the form Rsin(x-a) (=Rsin(x)cos(a)-Rcos(x)sin(a)). Looking at the original equation Rcos(a) = 2 and Rsin(a) = 1.5. Tan(a)=1.5/2 and R^2= 2^2 +1.5^2. Therefore R = 2.5 and a = 0.6435.Th...
Write out the product rule: if y=f(x)g(x) where f and g are functions, dy/dx = f'(x)g(x) + f(x)g'(x)Substitute in the expressions from the question:Therefore if f(x)=cos(3x) and g(x) = cosec(5x), f'...
First thing you would do is write down the coordinates where the tangent meets the curve. After that you would differenciate the equation (f(x)) of the curve (do dy/dx) in order to get f'(x).Then you woul...
We can denote the sides of the rectangle with a and b. As one side of the separated area is going to be the wall of the house, we do not have to use a fence there. Therefore, we will have two sides, one ...
←
219
220
221
222
223
→
Internet Safety
Payment Security
Cyber
Essentials